2017
DOI: 10.1038/npp.2017.153
|View full text |Cite
|
Sign up to set email alerts
|

Accumbens Mechanisms for Cued Sucrose Seeking

Abstract: Many studies support a perspective that addictive drugs usurp brain circuits used by natural rewards, especially for the dopamine-dependent reinforcing qualities of both drugs and natural rewards. Reinstated drug seeking in animal models of relapse relies on glutamate spillover from cortical terminals synapsing in the nucleus accumbens core (NAcore) to stimulate metabotropic glutamate receptor5 (mGluR5) on neuronal nitric oxide synthase (nNOS) interneurons. Contrasting the release of dopamine that is shared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…Our present data are in agreement with previous findings using adult rats wherein EtOH or NIC exposure did not cause any changes in GLT-1 expression in the PFC (Knackstedt et al, 2009, Goodwani et al, 2015). In addition, a recent study found that blocking GLT-1 in the NAc did not attenuate reinstatement of SUC seeking (Bobadilla et al, 2017). It is noteworthy that the present study provided some corroboration for the latter finding, such that chronic exposure to SUC did not affect GLT-1 expression in the NAc, HIP, or PFC.…”
Section: Accepted Manuscript 17supporting
confidence: 93%
“…Our present data are in agreement with previous findings using adult rats wherein EtOH or NIC exposure did not cause any changes in GLT-1 expression in the PFC (Knackstedt et al, 2009, Goodwani et al, 2015). In addition, a recent study found that blocking GLT-1 in the NAc did not attenuate reinstatement of SUC seeking (Bobadilla et al, 2017). It is noteworthy that the present study provided some corroboration for the latter finding, such that chronic exposure to SUC did not affect GLT-1 expression in the NAc, HIP, or PFC.…”
Section: Accepted Manuscript 17supporting
confidence: 93%
“…Rats that completed 15–20 days of FR training and were stable on the FR5 schedule for at least 3 days, continued on to subsequent studies. Mouse self-administration sessions (2hr) were performed at the same time each day during the dark phase as described previously (Bobadilla et al, 2017). Briefly, drug or sucrose availability was signaled both by the house light and a light above the active nose poke hole.…”
Section: Star Methodsmentioning
confidence: 99%
“…Self-administration models can also include measures of use escalation, withdrawal, extinction learning, and relapse, thus incorporating many features of OUD (28,29). In addition, rodents can be trained to self-administer natural rewards, such as sucrose, and neuroadaptations occurring during self-administration, extinction, or reinstated seeking of natural rewards can be compared with neuroadaptations observed in animals trained to self-administer opioids (30). In this review, we focus on the pathophysiology induced by noncontingent and self-administered opioids and cue-induced opioid seeking, where the neurobiological adaptations are not confounded by acute drug pharmacology.…”
Section: Preclinical Models Of Opioid Addictionmentioning
confidence: 99%